2016
DOI: 10.1111/jam.13256
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of acute hepatopancreatic necrosis disease Pir AB ‐like relies on secreted proteins not on gene copy number

Abstract: The secreted proteins of Vp_PirAB-like are key factors of virulence in the V. parahaemolyticus AHPND-causing strain, but not gene copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…In this study, no clear relation was observed between the bacterial density, measured as optical density, and the strain virulence. The virulence of Vp causing AHPND possibly depends on the concentration of the PirAB toxin (Tinwongger et al, 2016) or intrinsic factors of the strain (Feng, Liu, Wang, Sun, & Pan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no clear relation was observed between the bacterial density, measured as optical density, and the strain virulence. The virulence of Vp causing AHPND possibly depends on the concentration of the PirAB toxin (Tinwongger et al, 2016) or intrinsic factors of the strain (Feng, Liu, Wang, Sun, & Pan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For each group, 30 shrimp were used and were divided equally into two groups (high and low dose) in 10‐L aquarium tanks after 2 weeks of feeding. Vibrio parahaemolyticus D6 (Tinwongger et al., ) was used for the challenge test by immersion at two doses: the final concentrations were 4.5 × 10 5 cfu/ml and 1.5 × 10 5 cfu/ml for the high and low doses respectively. Another immersion challenge test was done after 12 weeks of feeding.…”
Section: Methodsmentioning
confidence: 99%
“…The cause of AHPND was identified as a strain of Vibrio parahaemolyticus that secretes toxins homologous to Photorhabdus insect‐related (Pir) toxins (Yang et al, ). These toxins were later confirmed as the virulence factors of the disease (Tinwongger et al, ).…”
Section: Introductionmentioning
confidence: 91%